2008
DOI: 10.1007/s00213-008-1373-7
|View full text |Cite
|
Sign up to set email alerts
|

Acid sensing ion channel (ASIC) inhibitors exhibit anxiolytic-like activity in preclinical pharmacological models

Abstract: These findings demonstrate that ASIC inhibition produces anxiolytic-like effects in some behavioral models and indicate a potential role for GABAergic mechanisms to underlie these anxiolytic-like effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
2
37
0
2
Order By: Relevance
“…However, a case-control twin study showed no association between polymorphisms of ASIC1 and anxiety spectrum disorders (175). Still, functional tests with ASIC inhibitors in animal models found that ASIC inhibition was able to produce antidepressive, sedative, and anxiolytic effects (88,112,234). For example, amiloride, PcTx1, and A317567 all exhibited anxiolytic activity, with PcTx1 and A317567 being most effective, most likely reflecting the lower potency of amiloride in ASIC inhibition (112).…”
Section: Asics and Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a case-control twin study showed no association between polymorphisms of ASIC1 and anxiety spectrum disorders (175). Still, functional tests with ASIC inhibitors in animal models found that ASIC inhibition was able to produce antidepressive, sedative, and anxiolytic effects (88,112,234). For example, amiloride, PcTx1, and A317567 all exhibited anxiolytic activity, with PcTx1 and A317567 being most effective, most likely reflecting the lower potency of amiloride in ASIC inhibition (112).…”
Section: Asics and Psychiatric Disordersmentioning
confidence: 99%
“…Still, functional tests with ASIC inhibitors in animal models found that ASIC inhibition was able to produce antidepressive, sedative, and anxiolytic effects (88,112,234). For example, amiloride, PcTx1, and A317567 all exhibited anxiolytic activity, with PcTx1 and A317567 being most effective, most likely reflecting the lower potency of amiloride in ASIC inhibition (112). The exact role and mechanism of ASIC in anxiety and fear learning remains to be elucidated, but the data suggest that inhibition of ASICs can play a role in the treatment of anxiety or depression states.…”
Section: Asics and Psychiatric Disordersmentioning
confidence: 99%
“…The choice of drug concentrations of amiloride was based on a previous study in vivo [14,15], which showed that at the doses of 100 and 200 mg/kg, amiloride suppressed limbic seizures in 33% of pilocarpine-treated animals, and reduced the seizure severity score in 67% of the remaining animals. These findings suggest that amiloride may modulate seizure generation and propagation, probably via mechanisms involving ASICs in the pilocarpine model of temporal lobe epilepsy.…”
Section: Animalsmentioning
confidence: 99%
“…Thus, it is necessary to develop a new generation of effective and better-tolerated anxiolytic agents. In this regard, Dwyer et al have shown that ASIC1a inhibitors have an effect in preclinical rodent models of autonomic and behavioral parameters of anxiety (Dwyer et al, 2009). In the stress-induced hyperthermia model, acute administration of ASIC inhibitors PcTX1, A-317567, and amiloride prevented stress-induced elevations in core body temperature.…”
Section: Asics and Anxiety Disordersmentioning
confidence: 99%